Metaheuristic applications in structures and infrastructures - Gandomi, Amir Hossein; Yang, Xin-She; Talatahari, Siamak; Alavi, Amir Hossein (Elsevier insights, 2013)
Due to an ever-decreasing supply in raw materials and stringent constraints on conventional energy sources, demand for lightweight, efficient and low-cost structures has become crucially important in modern engineering design.